Sunshade Sizing According to Bioclimatic Zones in Peru - Wieser, Martin (2024)
/External solar protection is one of the most important bioclimatic strategies in hot and temperate climates to avoid indoor overheating and the consequent thermal discomfort for dwellers. This document aims to objectively identify the times of the year and of the day when solar protection should be considered, depending on the building’s climate and location latitude in Peru. In addition to identifying ideal orientations and helping in sunshade sizing, the procedure has evidenced the need to recover the shading culture in the window openings in a particularly diverse and singular setting such as the Peruvian territory.